2005
DOI: 10.1073/pnas.0502249102
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphatemia leads to rickets by impairing caspase-mediated apoptosis of hypertrophic chondrocytes

Abstract: Rickets is seen in association with vitamin D deficiency and in several genetic disorders associated with abnormal mineral ion homeostasis. Studies in vitamin D receptor (VDR)-null mice have demonstrated that expansion of the late hypertrophic chondrocyte layer, characteristic of rickets, is secondary to impaired apoptosis of these cells. The observation that normalization of mineral ion homeostasis in the VDR-null mice prevents rachitic changes suggests that rickets is secondary to hypocalcemia, hypophosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
171
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(193 citation statements)
references
References 38 publications
9
171
0
5
Order By: Relevance
“…Nevertheless, the growth plate remained somewhat enlarged, and the cellular architecture, particularly in the hypertrophic zone, was disorganized. However, in the Casr À/À 1a(OH)ase À/À animals on a rescue diet, vitamin D deficiency still was present, and hypophosphatemia, which has been reported to impair caspase-mediated apoptosis of hypertrophic chondrocytes, (25) also persisted. Therefore, the fact that complete normalization of the growth plate did not occur may indicate that persistent hypophosphatemia and absent active vitamin D precluded complete recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the growth plate remained somewhat enlarged, and the cellular architecture, particularly in the hypertrophic zone, was disorganized. However, in the Casr À/À 1a(OH)ase À/À animals on a rescue diet, vitamin D deficiency still was present, and hypophosphatemia, which has been reported to impair caspase-mediated apoptosis of hypertrophic chondrocytes, (25) also persisted. Therefore, the fact that complete normalization of the growth plate did not occur may indicate that persistent hypophosphatemia and absent active vitamin D precluded complete recovery.…”
Section: Discussionmentioning
confidence: 99%
“…3 A-C). Normally, apoptosis is observed only in highly differentiated hypertrophic chondrocytes at the border of the primary spongiosa (11). We observed an increase in the number of TUNEL-positive cells at the expected location at the end of the hypertrophic layer of the Coll2-CreER T :PPR fl/fl mice at 4 d after administration of Tam [TUNEL-positive cells in the hypertrophic region (%): 4.11 ± 0.82 vs. 3.51 ± 0.78, n = 5 in each group], and we also observed TUNEL-positive cells in the region of columnar chondrocytes not seen in those cells in PPR fl/fl control mice (1.66 ± 0.53 vs. 0.04 ± 0.04; P < 0.05; n = 5 in each group) (Fig.…”
Section: Postnatal Ablation Of the Ppr In Growth Plate Chondrocytes Cmentioning
confidence: 99%
“…To examine the relationship between apoptosis and growth plate disappearance, we used an in vivo model known to suppress apoptosis of late hypertrophic chondrocytes. Sabbagh et al (11) showed that low levels of inorganic phosphate in the blood lead to suppression of apoptosis of late hypertrophic chondrocytes and expansion of the hypertrophic chondrocyte layer (rickets). To determine whether hypophosphatemia could suppress apoptosis in the absence of PPR signaling and, if so, whether this suppression mitigated the phenotype of the PPR KO mice, we subjected Coll2-CreER T : PPR fl/fl and PPR fl/fl control mice to a low-phosphate diet.…”
Section: Effects Of Phosphate Deprivation On the Growth Plate Abnormamentioning
confidence: 99%
“…The development of rachitic changes in this model paralleled the development of impaired chondrocyte apoptosis and hypophosphatemia, which lends further credence to the hypothesis that hypophosphatemia leads to rickets by impairing apoptosis of late hypertrophic chondrocytes. 10 It is interesting to note that in the models examined, impaired apoptosis was observed at a time when there was still considerable mineralized matrix surrounding the late hypertrophic chondrocytes, which suggests that circulating, rather than locally deposited, phosphate is the critical determinant of apoptosis. Supporting this hypothesis is the observation that tissue-nonspecific alkaline phosphatase-knockout mice (a model for the human disease hypophosphatasia) have normal circulating phosphate levels, have markedly impaired matrix mineralization, and do not develop rickets.…”
mentioning
confidence: 99%
“…To address this issue, studies were performed to characterize the growth-plate phenotype in 2 additional murine models: diet-induced hypophosphatemia/hypercalcemia and the hyp mouse (which has a mutation in the PHEX gene and is the murine model for the human disease X-linked hypophosphatemia). 10 The mice with hypophosphatemia in the presence of hypercalcemia (and suppressed PTH levels) and the hyp mice (normal calcium and PTH levels) both demonstrated expansion of the late hypertrophic chondrocyte layer associated with impaired apoptosis of these cells, which points to hypophosphatemia as the common etiologic factor. …”
mentioning
confidence: 99%